The HLA-G 14-bp Insertion/ Deletion Polymorphism in Recurrent Spontaneous Abortion among Iranian Women - Fateme Afkhami; Mahmoud Shekari Khaniani; Layia Farzadi; Zeynab Paknejad; Sima Mansoori Derakhshan (Iranian Journal of Allergy, Asthma and Immunology, 2014)
HLA-G is a non-classical HLA class Ib molecule with limited protein variability generated by  alternative  splicing.  HLA-G   displays  immunotolerant   properties  and  hence  plays important roles in the maintenance of a successful pregnancy and maternal tolerance of the semiallogenic fetus. Polymorphism of the HLA-G gene may potentially affect the biological properties of the protein, and a 14-bp insertion/deletion polymorphism in exon 8 of the 3′ untranslated region (3′ UTR) of the HLA-G gene is thought to influence HLA-G expression. To study the association of the 14-bp insertion/deletion (INDEL)  polymorphism with the risk of recurrent spontaneous abortion (RSA), we used polymerase chain reaction (PCR) amplification, and genotyped 85 women in the case group (women who have had two or more unexplained RSA) and 85 women in the control group (women who have had at least one normal pregnancy). Our results showed that the frequencies of the−14 bp/−14 bp and +14 bp/+14 bp genotypes were reduced in women with RSA, while that of the +14 bp/−14 bp genotype was significantly increased in RSA compared with the control group of normal fertile women; no  significant differences in the  allele frequencies of  the  HLA-G  14-bp polymorphism were observed. These results suggest a possible significance of the HLA-G 14-bp INDEL polymorphism in the outcome of pregnancy. However, further studies on other polymorphic sites in the 3 UTR  and  5′  UTR  regions, as well as monitoring  the  serum  HLA-G  concentration  are necessary in order to determine the potential implications of this marker in our population.